Houses think green! - Mira, Oscar.;Minguet, Josep Maria (Barcelona, Spain : Instituto Monsa de Ediciones, S.A., 2013)
The basic goals of the sustainability are based on reducing the consumption of non-renewable resources, minimizing the waste and creating healthy and productive environments. This volume illustrates vividly the current collaboration between modern architecture, contemporaneous inner design, committed landscaping and environmental responsibility. It is an innovating book presents ecological and sustainable dwellings; residences which add the sustainable design at the service of the quality design, as a premise on equal terms to sustainability. Each project is presented through a vast full-color photography collection, maps, details, schemes and diagrams or the solutions provided; ideas created by architects who are environmental conscious who have achieved practical, surprising and innovating solutions, adapting the program and the tastes and needs of their clients to the environment.
Velux Atika -- Rainshine house -- Barksdale residence -- Glass house -- Camouflage house -- English residence -- Eco-sustainable house -- Pool house -- Casa Locarno -- Hsu house -- Cliff house.
Keywords: ECOLOGICAL HOUSES